Analysis Comparative of Chinese and Indonesia Pronouns - Yi Ying (Bina Nusantara University, 2011)
Personal pronouns in communication plays a significant role. Proper use of personal pronouns, communication can proceed smoothly. Misuse of personal pronouns, or failure of communication will be blocked, or even make the communication between two sides break up. Therefore, understanding the language of the two personal pronouns is very important. This study analyzes the Chinese and India and usage of the classification of personal pronouns. Conclusion of the study hope to promote cross-cultural language communication, in particular, help to learn Chinese or learn Bahasa Indonesia in different occasions to use the correct pronouns. The results: (1) Chinese and Bahasa first person pronoun